Strategi Pengurus BAPQAH SIKA dalam Membina dan Meningkatkan Kualitas Qari Qariah dan Hafiz Hafizah di Sumatera Utara - Gorat, Rustam Effendi; Hasibuan, Wildan Anshori; Julyanda, Fanny; Nasution, Abdullah Habib (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research aims to analyze the coaching strategies carried out by the management of the Qari Qariah and Hafiz Hafizah Development Agency (BAPQAH SIKA) North Sumatra in improving the quality of students. Through qualitative descriptive methods, this research examines a systematic approach which includes motivation, class distribution systems, teaching methods, and communication with stakeholders. Data collection was carried out through interviews, observation and documentation studies. The research results show that BAPQAH SIKA implements a comprehensive strategy by dividing classes based on individual abilities, special teaching methods for each field (qari, hafiz, calligraphy), and building a supporting ecosystem through the involvement of parents and the community. Despite facing various challenges such as limited infrastructure and resources, BAPQAH SIKA succeeded in producing outstanding graduates at various national and regional Musabaqah Tilawatil Qur'an (MTQ) events. This research provides theoretical and practical contributions in developing strategies for developing Al-Qur'an education at the regional level.